Treatment of Cholera El Tor with Bactrim - S. Komalarini; J. Iswandari (Paediatrica Indonesiana, 1975)
Between November 1971 and May 1974, there were 41 children, comprising 26 boys and 15 girls, suffering from cholera El Tor gastroenteritis treated with parenteral Bactrim during the first 24 hours followed by Bactrim orally for 4 consecutive days. Rectal swabs on admission showed positive V. cholera biotype El- Tor cultures in all cases; 9 children had additional pathogenic E. coli in the stools. Besides Bactrim, treatment consisted of intravenous administration of lactated Ringer’s solution, dextrose 5% or saline. All the patients showed quick improvement of the clinical condition. Good result was found in 34 children (82.9%), fair in 6 (14.6%), and failure in 1 case (2.4%). All the children in this study survived. No drug intolerance or side effect was observed.